Effect of Black Glutinous Rice Fermented Beverage on Short-Chain Fatty Acid Levels in Metabolic Syndrome Rats - Nafisa, Putri Amalina; Nurwati, Ida; Putranto, Wachid (Majalah Obat Tradisional, 2024)
Metabolic Syndrome (MetS) represents a combination of metabolic factors that can elevate the likelihood of developing type 2 diabetes mellitus (T2DM) and coronary heart disease (CHD). The high prevalence of MetS results in a significant socio-economic burden. However, current management approaches have limitations, prompting the exploration of functional foods and nutraceuticals as promising alternatives. The primary objective of this study is to investigate the impact of Black Glutinous Rice Fermented Beverage (BGRFB) on Short Chain Fatty Acids (SCFA) concentration in a MetS rat model. Rats were induced with a high-fat diet (HFD) and streptozotocin (STZ)-nicotinamide (NA) to induce MetS conditions. BGRFB was administered as a treatment to the MetS rat group. The results showed that the Negative Control (NC) group exhibited a significant decrease in SCFA levels compared to the normal group (N). However, administration of BGRFB to the T2 group resulted in a significant increase in SCFA levels. The SCFA levels in the T2 group were higher but not significantly different from the Positive Control (PC) group treated with metformin. Increasing SCFA production could be an effective strategy in addressing Mets. This study demonstrates the potential of BGRFB as a therapy to enhance SCFA production and improve MetS. The outcomes of this investigation are anticipated to provide insights into novel dietary approaches for MetS management.